Improved INFORM method by minimizing the inverter nonlinear voltage error effects - Xie, G.; Lu, K.; Dwivedi, Sanjeet Kumar; Rosholm, J. (2015)
© 2015 IEEE.The INFORM (Indirect Flux detection by Online Reactance Measurements) method is regularly used for estimating the rotor position in PMSM sensorless drive systems at low speed and standstill. However, the estimation accuracy of the rotor position highly depends on how accurately the desired injection voltage vector may be produced. In this paper, a new method for generating the desired injection voltage vector is proposed. The nonlinear voltage error will be limited to one phase only, allowing an easy compensation. The performance of the INFORM method with the proposed voltage injection method is demonstrated experimentally. Comparison to the traditional voltage vector generation method is given as well.